Pengembangan Media Permainan Monopoli Guna Meningkatkan Hasil Belajar IPS Kelas V Sekolah Dasar - Firda Hidayatul Khasanah; Ratih Asmarani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
The development of monopoly game media to improve the learning outcomes of Class V students based on several gaps including: 1) students haven’t carried out learning interesting educational media, 2) there is no available learning that provides flexibility for students, 3) The average KKM has not the standard criteria. The development of media uses the Borg and Gall model modified as needed. There are 10 processes that implemented study, namely, 1) potential and problems, 2) gathering information, 3) product design, 4) design validation, 5) design improvement, 6) product testing, 7) product revision, 8 ) use trial, 9) final product revision, 10) mass production. The results research show that the percentage from the instrument validator is 93.8% very valid category, media validator is 92% very valid and suitable for use without improvement, material validator is 83.75% valid category and suitable for use without improvement but there are still revisions. The test results of educators are 87.4% eligible category. The results of small group trials were conducted 6 students percentage of 87.3% in the very attractive category, field trials were carried out 15 students percentage of 87.6% in the very attractive category. The results T-Test from the small group for the Pre-Test results were 63.3 and the Post-Test results obtained an average of 99.3. Meanwhile, for the second group, the average Pre-Test was 64.1 and the Post-Test result was 98.6. Based on the results of the overall data analysis, it can be concluded that the development of media monopoly game is feasible to be used as a learning medium. Keywords: Monopoly media, Social Science